2016
DOI: 10.1038/nrm.2016.140
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic regulation of gene expression through histone acylations

Abstract: Eight types of short-chain lysine (Lys) acylations have recently been identified on histones: propionylation, butyrylation, 2-hydroxyisobutyrylation, succinylation, malonylation, glutarylation, crotonylation and β-hydroxybutyrylation. Emerging evidence suggest that these histone modifications affect gene expression and are structurally and functionally different from the widely studied histone Lys acetylation. In this review, we discuss the regulation of non-acetyl histone acylation by enzymatic and metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
801
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 800 publications
(818 citation statements)
references
References 105 publications
(163 reference statements)
13
801
0
4
Order By: Relevance
“…Since the rates of crotonylation, butyrylation, and propionylation by p300 are extremely low (3-fold to as much as 62-fold) in comparison to acetylation, 34 there may be a metabolic component that involves increasing short chain acyl-CoA concentrations and/or a non-enzymatic mechanism to regulate the diversity and levels of protein lysine acylations. 35, 36 Methylation of H4K5 exists in vivo and is catalyzed by the lysine methyltransferase SET5 in yeast and by the SET and MYND domain-containing protein 3 (SMYD3) in human. 37, 38 Moreover, while SMYD3 is able catalyze mono-, di-, and trimethylation of H4K5 as well as monomethylation of H4K12, the major product of SMYD3 is monomethylated H4K5.…”
Section: Introductionmentioning
confidence: 99%
“…Since the rates of crotonylation, butyrylation, and propionylation by p300 are extremely low (3-fold to as much as 62-fold) in comparison to acetylation, 34 there may be a metabolic component that involves increasing short chain acyl-CoA concentrations and/or a non-enzymatic mechanism to regulate the diversity and levels of protein lysine acylations. 35, 36 Methylation of H4K5 exists in vivo and is catalyzed by the lysine methyltransferase SET5 in yeast and by the SET and MYND domain-containing protein 3 (SMYD3) in human. 37, 38 Moreover, while SMYD3 is able catalyze mono-, di-, and trimethylation of H4K5 as well as monomethylation of H4K12, the major product of SMYD3 is monomethylated H4K5.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous CoA thioesters are also involved in the post-translational modification of histones and thousands of other proteins (1)(2)(3)(4)(5). Three major subcellular CoA pools are found in the cytosol, mitochondria, and peroxisomes to support specific metabolic pathways (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…These include, among others, fatty acid synthesis in the cytosol, the TCA cycle and oxidation of longchain and medium-chain fatty acids in the mitochondria, and bile acid conjugation and oxidation of very long-chain and branched-chain fatty acids in the peroxisomes. A dedicated pool of acetyl-CoA is also found in the endoplasmic reticulum where it is involved in protein quality control and autophagy (8), while nuclear acylCoAs, which freely equilibrate with the cytosolic pool across the nuclear pores, contributes to the regulation of gene expression (5).…”
Section: Introductionmentioning
confidence: 99%
“…The result suggests that the transcription elongation machinery could be an effective therapeutic target. It was recently reported that ENL protein, which possesses acetyl lysine recognizing YEATS domain [30], acts as an activator of leukemia-diving factor encoding gene expression [53,54]. Therefore, targeting the ENL protein could be an effective therapeutic strategy against aggressive leukemia.…”
Section: Transcription Disorders and Human Diseasesmentioning
confidence: 99%
“…In addition, they are acylated on the Lys residues to regulate transcription of genes that encode metabolic-response factors [30]. These modifications are recognized by different proteins, such as bromodomaincontaining proteins [31], double PHD finger domain proteins [30,32], YEATS domain proteins [30], WD40 proteins [33], and Ankyrin-repeat proteins [34].…”
Section: Epigenetic Control Of Gene Expressionmentioning
confidence: 99%